Dinamika Peran Human Resources Business Partner (HRBP) dalam Mendrive Strategi Bisnis : Studi Kasus pada Perusahaan Sektor Finansial di Indonesia - Ahmad Farabi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to explore the dynamics of the role of Human Resources Business Partners (HRBPs) in driving business strategy, with a focus on identifying challenges and supporting factors for their implementation in the Indonesian financial sector. The study employed a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with several HRBPs and line managers in financial sector companies, supported by observation and document analysis. The collected data were analyzed thematically. The results revealed three main challenges faced by HRBPs: (1) resistance to change within the HR function itself, (2) limited analytical and business competencies within HRBPs, and (3) a lack of understanding of the strategic role of HRBPs among line managers. Furthermore, the success of the HRBP role is strongly supported by three key factors: full support from top management, quality collaboration with line managers, and the use of information technology for efficiency and data analysis. This study provides practical guidance for companies, particularly in the financial sector, to optimize the strategic role of HRBPs through competency development programs, organizational culture change, and technology support. This research provides an in-depth empirical overview of the actual practices and complexities of implementing the HRBP model in the Indonesian context, a topic rarely explored.